The Impact of Ownership Structure and Board of Directors’ Characteristics on Tax Avoidance: Evidence from Jordan - Abu Nassar, Mohammad (Jordan Journal of Business Administration, 2025)
This study aims to examine the effect of ownership structure and board of directors’ characteristics on tax avoidance for Jordanian industrial companies listed in the Amman Stock Exchange from 2010 to 2020. In light of this, two variables were used to measure tax avoidance in Jordan: the effective tax rate (ETR) and the book tax differences (BTD), while three variables were used to measure the ownership structure: family ownership, foreign ownership and management ownership. The board of directors’ characteristics were measured through five variables: board independence, women in board, board size, foreign directors and the percentage of members of the board of directors with a Ph.D. The hypotheses of the study were tested using two models, where the results of the first model, in which tax avoidance was measured through the actual tax rate, indicate that increasing of foreign ownership, women in board, company size, the rate of return on equity and enterprise value (Tobin’s Q) reduces tax avoidance. In contrast, the results indicate that increasing each of management ownership in the company, the rate of non-Jordanians in the board of directors and the debt ratio increases tax avoidance. The results of the second model test, in which tax avoidance was measured using book tax differences, indicate that the increase in family ownership, company size and the rate of return on equity reduces corporate tax avoidance, whereas the increase in foreign directors, debt ratio, management ownership and women in the board of directors increases corporate tax avoidance.